Assessment of jeepney in terms of ergonomics, safety and environmental factors for the development of specifications and standards - Bacero, Riches S. (2009)
This research assessed the jeepney vehicle in terms of ergonomics, safety and environmental factors. It established database of manufacturers and their design specification, determined the condition and design of the vehicle based on the perception and preference of jeepney drivers and passengers, and compared the parts of the jeepney vehicle using Philippine National Standards (PNS) and international standards. The research provided essential information for the development of jeepney's specifications and standards. The study revealed that most jeepney manufacturing firms have varied specifications with regard to the capacity, dimensions and weight of the vehicle. Most of the jeepney drivers and passengers want to improve, change and standardize the parts of the jeepney vehicle. In addition, the parts of jeepney vehicles have similar specifications compared to the 4 out of 5 mandatory PNS and 22 out of 32 UNECE Regulations applicable to the jeepney vehicle. It is concluded that the jeepney vehicle can be standardized in terms of design, safety and environmental concerns.
"May 2009."
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman.
Keywords: Jeep automobile; Motor vehicles -- Standards -- Philippines; Human engineering